Measurement and analysis of multiband bistatic and monostatic radar signatures of wind turbines. Issue 14 (1st July 2015) - Ritchie, M.; Fioranelli, F.; Balleri, A.; Griffiths, H.D.
Abstract : The results of recent measurements taken with two radar systems to measure the simultaneous monostatic and bistatic signature of wind turbines, at S‐band and X‐band are presented. Coherent monostatic and bistatic data was collected with the University College London (UCL) NetRAD 2.4 GHz radar, and the Cranfield University CW radar operating at X‐band. Initial analysis shows the bistatic Doppler signature of wind turbines and informs on the key differences seen at modest bistatic angles. Polarimetric variations are also analysed via data gathered from using co‐polarised VV and HH and cross‐polarised VH components.